Peran Komunikasi Efektif dalam Mengurangi Stres pada Mahasiswa di STIE Pembangunan Tanjungpinang - Nunung Marleni; Retno Widowati; Risma Selvi Dewi; Fery Prayoga Saputra; Jovi Saputra (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the role of effective communication in helping students manage stress at STIE Pembangunan Tanjung Pinang. Effective communication allows students to communicate their thoughts and feelings clearly, get emotional support and find solutions to the problems they face. The study used a qualitative approach through semi-structured interviews with six academically active students. Results showed that students who were open to communication felt more secure and tended to be better able to manage stress. Conversely, students who tended to be withdrawn were more susceptible to the negative effects of stress physically, emotionally, cognitively and behaviorally. The study concluded that effective communication plays an important role in reducing students' stress and recommends that educational institutions help students develop their communication skills through training and mentoring programs.